An Improved Remote Sensing Image Classification Based on K-Means Using HSV Color Feature - Wu, Shulei; Chen, Huandong; Zhao, Zhizhong; Long, Haixia; Song, Chunhui (2014 Tenth International Conference on Computational Intelligence and Security, 2014)
An improved classification method based on KMeans using HSV color feature is introduced in this paper. It is implemented by extracting three color features (hue, saturation, value) for K-Means clustering. Compared with the traditional K-Means clustering, the experimental results turn out that our proposed method is better than K-Means in classification accuracy and performance.